BIOMASSADAN GELIOPIROLIZ USULIDA YOQILG‘I OLISH TAJRIBA QURILMASINING PARAMETRLARINI ASOSLASH - Almardanov, Hamidulla; Chuliyev, Siroj (Innovatsion texnologiyalar, 2022)
Based on this article the parameters of the experimental device have been presented for obtaining alternative fuel from biomass by the heliopyrolysis method. In addition, in this article, the principle scheme of the experimental device was developed for thermal processing of biomass and obtaining alternative solid, liquid and gaseous fuel. Calculations and theoretical studies obtained in the process of solar concentrator heliopyrolysis determined the amount of energy that can be generated by concentrators using the Aparasi formula and Gaussian distributions.